Structure and activity alteration in adult highland residents' cerebrum: Voxel-based morphometry and amplitude of low-frequency fluctuation study - Zhong, Minzhi; Zeng, Huaqu; Wang, Dongye; Li, Jiesheng; Duan, Xuguang; Li, Yong (Frontiers in Neuroscience, 2022)
Introduction People living in highland areas may have factors that allow them to adapt to chronic hypoxia, but these physiological mechanisms remain unclear. This study aimed to investigate the brain mechanism in a cohort of adult residents of Tibet, a well-known plateau section in China, by observing differences in brain structure and function in non-plateau populations. Methods The study included 27 Tibetan and 27 non-plateau region residents who were matched in age, sex, and education. All participants underwent high-resolution three-dimensional T1 weighted imaging (3D-T1WI) and resting-state functional magnetic resonance imaging (rs-fMRI) scans on a 1.5 Tesla MR. Gray matter volumes and regional spontaneous neuronal activity (SNA) were calculated and compared between the two groups. Results When comparing gray matter in people living in high altitudes to those living in the flatlands, the results showed positive activation of gray matter in local brain regions (p < 0.05, false discovery rate (FDR) corrected), in the right postcentral [automated atomic labeling (aal)], left postcentral (aal), and right lingual (aal) regions. Comparing the people of high altitude vs. flat land in the brain function study (p < 0.05, FDR corrected), positive activation was found in the right superior motor area (aal) and left superior frontal (aal), and negative activation was found in the right precuneus (aal). Conclusion In high-altitude individuals, larger regional gray matter volumes and higher SNA may represent a compensatory mechanism to adapt to chronic hypoxia.